Forage and crop trials in the southern rangelands, 1985 and 1986 - Migongo-Bake, W. (International Livestock Centre for Africa, 1986)
The report describes and discusses results of forage work conducted in the southern rangelands of Ethiopia between 1985 and 1986 with the aim of identifying legume species that perform well under the prevailing climatic conditions and that is then considered for introduction into pasture and cropping system of the Borana people to elevate the nutritional stress of livestock during the dry season.